METODE BIBEL DALAM PEMAKNAAN AL-QUR’AN (Kajian Kritis terhadap Pandangan Orientalis) - Yusup, Asdar (Hunafa: Jurnal Studia Islamika, 2016)
Orientalist’s attention against the Quran can be traced since the visit of Peter Venerable, from Cluny, to Toledo in the mid 12th century. He asked some western scholars to produce a series of works that will be a scientific basis for the western intellectual meeting with Islam. Orientalist’s critical study against the Quran is not limited to questioning its authenticity. The issues raised are the classic that is always a matter of the influence of Jews, Christians, Zoroastrians, and the contents of the Quran. Orintalist then snaring to a naïve assumption that the Quran is the historical product. Orientalist’s biggest mistake was to assume the Quran equal to the bible. When a critical study of the bible to prove some of its contents are not original anymore, so they assumed that a critical assessment of the Quran to prove the same thing. Though, the biblical method proved the originality of the quran. Therefore, their desire to make a critical edition, and restore the text of the Quran is closer to a fantasy rather than a scientific work